Evaluation of the partnership and cooperation agreement between the European Union And Russia from the public diplomacy of perspective - (:unkn) unknown (My University, 2011)
Bu makale, Soğuk Savaş sonrası dönemde Avrupa Birliği ve Rusya arasındaki ilişkilerin temel dayanağını oluşturan Ortaklık ve İşbirliği Antlaşmasını Rus kamu diplomasisi açısından değerlendirmektedir. Bu çalışmada, Avrupa Birliği ile Rusya arasındaki ilişkilerin hukuki, kurumsal ve siyasi çerçevesini oluşturan Ortaklık ve İşbirliği Antlaşması çeşitli yönleriyle ele alınmıştır. Aynı zamanda stratejik bir ortaklık kurma söylemleri de farklı boyutlarıyla incelenmiştir. Avrupa Birliği ve Rusya arasındaki ilişkilerin gelişmesine yönelik mekanizmalara sahip olmasından dolayı Ortaklık ve İşbirliği Antlaşmasının değerlendirilmesi tercih edilmiştir. Ortaklık ve İşbirliği Antlaşması'nın en hassas ve kırılgan alanını oluşturan siyasi ortaklığın, belgelerde yazıldığı gibi uygulanmadığı ve söylemde kaldığı tespit edilmiştir. Yani Rusya ve Avrupa Birliği ilişkileri, bazı problemli siyasi konulardan dolayı, belgelerde amaçlandığı ve söylendiği gibi başarıya ulaşamamıştır.

This article evaluates the Partnership and Cooperation Agreement between the European Union and Russia from a Russian perspective of public diplomacy after the Cold War. Partnership and Cooperation Agreement is the legal basis for EU relations with Russia. It establishes the institutional and political frameworks for bilateral relations, sets the principal common objectives, calls for activities and dialogue in a number of policy areas and provides an appropriate mechanism for political dialogue. This study discusses why the relationship between the European Union and Russia has not achieved its intended aims as indicated in the documents and what the leaders says. On the other side, Russia has shown this agreement as a success in terms of public diplomacy. It is also examined the current rhetoric of Europe and Russia to build a strategic partnership. Within the context of this article it is determined that the most sensitive and vulnerable area of cooperation in the framework of the Partnership and Cooperation Agreement (PCA) is the political partnership which has not realized as in the rules and the rhetoric in programmatic documents due to some trouble political issues.
Rusya ile Avrupa birliği arasındaki ortaklık ve işbirliği antlaşmasının Rus kamu diplomasisi perspektifinden değerlendirilmesi
Keywords: Uluslararası İlişkiler; Siyasi Bilimler